Diálogo no ensino da matemática: participação do aluno no processo de ensino-aprendizagem - Feitosa, Walter Fabiano Santos (2023)
Mathematics teachers are challenged to (re)create teaching strategies to obtain satisfactory results in student learning, among which dialogue in the educator-student interaction stands out. This research aims to analyze the student's dialogical participation in the learning process in mathematics classes when studying specific Mathematics content, guided by the following guiding question: What are the implications of dialogue in the teaching-learning process of Mathematics? With this theoretical-methodological orientation, the research seeks to contextualize the teaching of Mathematics carried out in the school environment, discussing the relevance of the interactional dialogue between educator and student in the teachinglearning process, as well as verifying the practice of the Mathematics teacher based on interactional dialogue. This is a case study carried out with Mathematics teacher and students in the first year of high school at the Olavo Bilac High School Reference School, focusing on the practice of interactional dialogue in the classroom. This discussion is based on the contributions of theorists such as Paulo Freire, who defends the dialogical relationship in the teacher's approach to students and between students, in order to reduce difficulties in learning the content of this discipline. The principles of Ethnomathematics helped us to profile the students participating in the research. It is a contribution used to understand the cultural and social universe of these young people, bridging the gap with dialogic practice in teaching mathematics, complementing our work proposal. To support the investigation, we rely on the theoretical and methodological references of Ethnomathematics and Mathematics Education. The production of research data was carried out through the use of questionnaires and observation of Mathematics classes. For the class teacher, mathematics teaching needs to be humanized, contextualized with the students' reality. The fact that caught our attention the most, and which was practically unanimous among the students interviewed, is the need to present mathematics as something really useful in their daily lives, avoiding the old questions “where or when will I use this in life?” Our research showed that dialogue played a key role in promoting students' self-confidence in their mathematical skills. The ability to discuss and explain their solutions contributed to increased confidence in solving mathematical problems. Dialogue provided a space in which students felt more encouraged to express their ideas, ask questions, and contribute to the discussion.